EFFECTIVENESS OF USING VIDEO COMPARED TO OTHER MEDIA FOR DENTAL AND ORAL HEALTH EDUCATION - Kusparmanto, Lukas; Yuditha, Solva (Moestopo International Review on Social, Humanities, and Sciences, 2023)
Dental health education for children aims to introduce them to the world of dental health and address issues related to teeth. One of the recommended method is through video viewing, which can captivate children's attention, particularly when animated videos are used. This study analyzes the effectiveness of video viewing in improving target knowledge and compares it with other methods. This research involved analyzing national and international books and journals that explore the use of videos as a teaching tool for dental health education among elementary school-age children. Results show videos are highly effective in enhancing children's knowledge of proper teeth brushing. They outperform other methods such as flip charts, leaflets, and posters. When compared to alternative educational methods, videos are almost as effective as hand puppets. However, flip charts, leaflets, and posters remain viable options for dental and oral health education among elementary school children, as they have proven to be effective.